Thermal and species transportation of Eyring-Powell material over a rotating disk with swimming microorganisms: applications to metallurgy - Rahila Naz; Fazle Mabood; Muhammad Sohail; Iskander Tlili (Journal of Materials Research and Technology, 2020)
Transportation of heat and mass for the bio-convective magneto-hydrodynamic flow of Eyring-Powel nanofluid flowing over a rotating disk is inspected in the current exploration which has applications in different industries. i.e. To enhance the thermal performance of the system, mixture of bioconvective is used along with nanofluids. Flow is produced due to the stretching of rotating disk. Phenomenon of heat and mass are developed by using traditional Fourier and Fick's laws respectively. Viscous dissipation is included in the thermal transport expression. Buongiorno model is considered to capture the involvement of Brownian motion and thermophoresis aspects by the presence of nanofluid. Boundary layer approximation is used to develop the expressions for the momentum, heat, mass and swimming gyrotactic microorganism's profiles. The derived boundary layer equations are converted into set of ordinary differential equations by engaging an appropriate transformation. These converted equations are solved numerically with the help of shooting method. Various graphs are prepared in order to inspect the bearing of influential parameters. Moreover, skin friction, heat transfer, mass transfer and density of motile microorganism are presented with the help of graphs and tables.